2007
DOI: 10.1016/j.pbb.2007.02.004
|View full text |Cite
|
Sign up to set email alerts
|

NMDA receptor in conditioned flavor-taste preference learning: Blockade by MK-801 and enhancement by D-cycloserine

Abstract: Conditioned flavor-taste preference (CFTP) is a robust form of learning in which animals acquire a preference for a flavor (e.g. Kool-Aid) previously mixed with a highly preferred tastant (e.g. fructose) over a flavor previously mixed with a less preferred tastant (e.g. saccharin). Here, the role of the Nmethyl-D-aspartate (NMDA) glutamate-glycine receptor (NR) was probed using systemic MK-801, a non-competitive antagonist, and D-cycloserine (DCS), a glycine agonist. Rats were injected with MK-801 (100 μg/kg) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
40
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 41 publications
5
40
1
Order By: Relevance
“…These data are highly consistent with the abilities of systemic MK-801 to eliminate the acquisition of fructose-CFP in rats (Golden and Houpt, 2007), and of amygdala administration of the competitive NMDA antagonist, AP-5 to eliminate the acquisition of CFP elicited by IG glucose (Touzani et al, 2013). The present study also demonstrated a clear strain difference in the potency of MK-801 to block the acquisition of sugar preferences.…”
Section: Accepted Manuscriptsupporting
confidence: 89%
See 2 more Smart Citations
“…These data are highly consistent with the abilities of systemic MK-801 to eliminate the acquisition of fructose-CFP in rats (Golden and Houpt, 2007), and of amygdala administration of the competitive NMDA antagonist, AP-5 to eliminate the acquisition of CFP elicited by IG glucose (Touzani et al, 2013). The present study also demonstrated a clear strain difference in the potency of MK-801 to block the acquisition of sugar preferences.…”
Section: Accepted Manuscriptsupporting
confidence: 89%
“…MK-801, eliminated fructose-CFP acquisition, but not expression (Golden and Houpt, 2007). Further, the competitive NMDA antagonist, AP-5 administered into the rat amygdala eliminated acquisition, but not expression of a CFP induced by IG glucose (Touzani et al, 2013).…”
Section: Accepted Manuscriptmentioning
confidence: 85%
See 1 more Smart Citation
“…Another neurotransmitter system implicated in flavor conditioning is the glutamatergic system. The non-competitive NMDA receptor antagonist, MK-801 was observed to reduce the acquisition, but not expression of fructose-conditioned flavor preferences, whereas the glycine agonist, D-cycloserine enhanced this response (Golden and Houpt, 2007). It may be that dopamine interacts with different neurotransmitter systems in mediating different aspects (e.g., acquisition, expression) of flavor-flavor preference learning.…”
Section: Discussionmentioning
confidence: 95%
“…The NMDA glutamate-glycine receptor has been implicated in flavor-flavor preferences in that the acquisition, but not the expression, of fructose-conditioned flavor preferences was respectively reduced by systemic administration of the non-competitive NMDA antagonist, MK-801, and enhanced by systemic administration of the glycine agonist, D-cycloserine (Golden and Houpt, 2007). Although the general opioid antagonist, naltrexone, is capable of reducing intakes of sucrose and saccharin solutions (see review, Bodnar, 2004), systemic administration of naltrexone failed to alter the acquisition or expression of sucroseconditioned flavor-flavor preferences in sham-feeding rats (Yu et al, 1999), of fructoseconditioned flavor-flavor preferences in real-feeding rats (Baker et al, 2004), or of sucroseconditioned flavor-nutrient preferences following IG infusions (Azzara et al, 2000).…”
Section: Introductionmentioning
confidence: 99%